Positive Leadership : Strategies for Extraordinary Performance - Cameron, Kim S. (BK Business., 2012)
This is the bestselling and leading introduction to the new field of positive leadership, which helps leaders in all types of organizations reach beyond ordinary success to achieve extraordinary effectiveness, spectacular results, and positively deviant performance.